Navigating Financial Distress: How Board Gender Diversity Moderates the Impact of Leverage and Total Asset Turnover - Anggraeni, Diah Ayu; Kushermanto, Andi; Ulum, Akhmad Samsul; Febryanti, Erika (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Purpose: This research aims to analyze the influence of leverage and total asset turnover on financial distress in non-cyclical consumer sector companies listed on the IDX, as well as the moderating role of board gender diversity in enhancing financial stability. Method: Using the SEM-PLS approach with WarpPLS 8.0, data from 113 companies during 2018–2022 were analyzed through purposive sampling. The moderating variable in the form of gender diversity on the board of directors was used to examine its influence on the strength and direction of the relationships between variables. Results: The results show that leverage has a positive effect on financial distress, while total asset turnover has a negative effect. Gender diversity on the board has been proven to weaken the negative impact of leverage and strengthen the positive impact of asset turnover on reducing distress. This shows that a gender-diverse board of directors plays an important role in enhancing the company's resilience by influencing financial health strategies. Implications: Gender diversity on the board of directors can be an effective strategy for risk mitigation and financial stability. These findings support the implementation of policies that promote inclusivity in corporate governance. This research emphasizes the potential of gender diversity to serve as a catalyst for more robust, transparent, and sustainable corporate governance practices. Novelty: This study fills the gap in previous research that produced inconsistent findings regarding the impact of total asset turnover and gender diversity independently. This research uniquely demonstrates that board gender diversity actively moderates the impact of leverage and asset efficiency on financial distress—particularly in emerging markets and the non-cyclical consumer sector.